Circadian Clocks, Stress, and Immunity - Dumbell, Rebecca; Matveeva, Olga; Oster, Henrik (Frontiers in Endocrinology, 2016)
In mammals, molecular circadian clocks are present in most cells of the body, and this circadian network plays an important role in synchronizing physiological processes and behaviors to the appropriate time of day. The hypothalamic-pituitary-adrenal endocrine axis regulates the response to acute and chronic stress, acting through its final effectors – glucocorticoids – released from the adrenal cortex. Glucocorticoid secretion, characterized by its circadian rhythm, has an important role in synchronizing peripheral clocks and rhythms downstream of the master circadian pacemaker in the suprachiasmatic nucleus. Finally, glucocorticoids are powerfully anti-inflammatory, and recent work has implicated the circadian clock in various aspects and cells of the immune system, suggesting a tight interplay of stress and circadian systems in the regulation of immunity. This mini-review summarizes our current understanding of the role of the circadian clock network in both, the HPA axis and the immune system, and discusses their interactions.